Rewriting the Future: How Metamodern Education Can Redefine Society and Leadership - Shtaltovna, Yuliya (GILE Journal of Skills Development, 2024)
This food-for-thought paper challenges traditional paradigms and proposes a metamodern framework for redefining the optics on the role of education in society, advocating for a new social contract rooted in shared values, inclusivity, and interdisciplinary collaboration. How can we democratize higher education and empower individuals to navigate the uncertainties of the 21st century? Is moving beyond fragmented knowledge and fostering skills-based education truly beneficial? Moving beyond postmodern fragmentation, metamodernism emphasizes cooperation and holistic development, presenting a blueprint for transforming society by bridging individual agency and collective progress. The Inner Development Goals (IDG) promotes skills-based and humanity-focused leadership that addresses the inner and outer dimensions of sustainable development. This transformative skills-based approach to leadership encourages educators and institutions to embrace complexity and ambiguity, preparing future leaders to leverage inherited chaos for meaningful change. This approach challenges traditional paradigms and calls for a dynamic interplay that aligns with the metamodern ethos.